2004
DOI: 10.1021/jp0456887
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for the Formation of a Chiral Template

Abstract: The chemisorptive enantioselectivity of propylene oxide is examined on Pd(111) surfaces templated by chiral 2-methylbutanoate and 2-aminobutanoate species. It has been found previously that chiral propylene oxide is chemisorbed enantiospecifically onto Pd(111) surfaces modified by either (R)-or (S)-2-butoxide. The enantiomeric excess (ee) varied with template coverage, reaching a maximum of ∼31%. Templating the surface using 2-methylbutanoate, where the chiral center is identical to that in the 2-butoxide spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
72
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 30 publications
3
72
0
Order By: Relevance
“…Herein, we consider a chiral Cu surface of the type that has been used in a number of experiments [15][16][17][18] and examine two molecular adsorbates, one of which, propylene oxide, has been used in several experimental studies of surface chirality. [1,16,19] We recently used DFT methods very similar to those used below to determine the structure of chiral adlayers of amino acids on low-index Cu surfaces and found very good agreement between the calculated structures and those observed experimentally. [20,21] Our calculations examined the adsorption of the amino-(fluoro)methoxy (FAM) species and propylene oxide on a Cu(874) surface.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Herein, we consider a chiral Cu surface of the type that has been used in a number of experiments [15][16][17][18] and examine two molecular adsorbates, one of which, propylene oxide, has been used in several experimental studies of surface chirality. [1,16,19] We recently used DFT methods very similar to those used below to determine the structure of chiral adlayers of amino acids on low-index Cu surfaces and found very good agreement between the calculated structures and those observed experimentally. [20,21] Our calculations examined the adsorption of the amino-(fluoro)methoxy (FAM) species and propylene oxide on a Cu(874) surface.…”
mentioning
confidence: 86%
“…PO has previously been used experimentally as a probe for enantiospecific binding on both intrinsically chiral metal surfaces [16] and chirally templated surfaces. [1,19] We first examined the adsorption of PO on Cu(111) and found that the molecule favors a configuration in which the terminal methyl group is oriented away from the surface. Test calculations with PO on Cu(874) S showed that PO binds much more strongly to step-edge sites than to terrace sites, so only adsorption configurations with the molecule above the step edge were considered further.…”
mentioning
confidence: 99%
“…One promising route for achieving this is to use chiral modifiers to endow enantioselective properties onto a metallic surface (Baiker and Blaser 1997). This modification of the surface may act selectively towards the adsorption of another chiral probe species in two ways: (a) through a oneto-one mechanism, either by the formation of a complex between an individual modifier molecule and the reactant or by the creation of a single selective site on one side of the modifier (Tungler et al 1989;Baiker 1997;LeBlond et al 1999;Bürgi and Baiker 2000;Kubota and Zaera 2001;Chu et al 2003;Ma and Zaera 2005) and (b) through a template mechanism, in which the chiral modifier adsorbs forming a superstructure, while the template which contains void spaces acts selectively on the adsorption of one of the enantiomers of the probe chiral species through symmetry effects (Raval 2001;Ortega Lorenzo et al 1999;Humblot et al 2004;Stacchiola et al 2002Stacchiola et al , 2005Romá et al 2004;Lee and Zaera 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In all these studies, chiral propylene oxide was used as the probe molecule to measure the enantioselective characteristics of the template. However, an understanding at a molecular level of the enantioselective process in a template system is far from being attained (Romá et al 2003(Romá et al , 2004Szabelski 2004;Szabelski and Sholl 2007a,b;López et al 2008). Some studies (Szabelski 2004;Szabelski and Sholl 2007a,b) have shown how enantioselectivity of a chiral species can arise on a substrate with a pattern of strong and weak adsorbing sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation